2007
DOI: 10.1021/ic7016787
|View full text |Cite
|
Sign up to set email alerts
|

Coordination “Oligomers” in Self-Assembly Reactions of Some “Tritopic” Picolinic Dihydrazone LigandsMononuclear, Dinuclear, Hexanuclear, Heptanuclear, and Nonanuclear Examples

Abstract: "Tritopic" picolinic dihydrazone ligands with tridentate coordination pockets are designed to produce homoleptic [3 x 3] nonanuclear square grid complexes on reaction with transition-metal salts, and many structurally documented examples have been obtained with Mn(II), Cu(II), and Zn(II) ions. However, other oligomeric complexes with smaller nuclearities have also been discovered and identified structurally in some reactions involving Fe(II), Co(II), Ni(II), and Cu(II), with certain tritopic ligands. This illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…[30] With decreasing temperature, the chiral space group P2 1 2 1 2 1 is unchanged and the cell dimensions decrease slightly. Investigation of the other crystals in the same batch revealed that the compound is composed of a racemic mixture of opposite handedness.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[30] With decreasing temperature, the chiral space group P2 1 2 1 2 1 is unchanged and the cell dimensions decrease slightly. Investigation of the other crystals in the same batch revealed that the compound is composed of a racemic mixture of opposite handedness.…”
mentioning
confidence: 99%
“…Neighboring iron ions are bridged by the single oxygen atoms of the ligand "edges" with M···M separations of approximately 3.8 and M-O-M angles of about 1308, facilitating the antiferromagnetic superexchange pathway. [31] On the other hand, since the coordination bond lengths around the Fe II centers differ for low-spin (LS) and high-spin (HS) states (Dd = 0.14-0.24 ), [32] LS and HS states can be identified by the metal-ligand bond length. In fact, at 123 K, the average FeÀN coordination bond lengths involving 2 , two possible spin geometries may exist, namely, HS species exist either on the same side (a cis structure) or on the diagonal (trans geometry) of the square.…”
mentioning
confidence: 99%
“…It effectively competes with nickel(II) in the sense that it occupies the central cavity with tight hydrogen bonding interactions to six ligand NH protons. 32 The reaction could in fact be regarded as an anion templated dinuclear assembly. Interestingly, in a similar reaction of 2popp with Fe(III) in the presence of PF 6 − , the same type of fluoride centered dinuclear structure results, but is also accompanied by reduction of Fe(III) to Fe(II).…”
Section: Oligomers and Other Possible Alternative Products To The 'Exmentioning
confidence: 99%
“…Interestingly, in a similar reaction of 2popp with Fe(III) in the presence of PF 6 − , the same type of fluoride centered dinuclear structure results, but is also accompanied by reduction of Fe(III) to Fe(II). 32 Higher order grid based oligomers have also been observed, and may represent logical intermediates en route to the assembly of a full [3 × 3] grid. [Ni 6 (Cl2poap) 5 ][Ni(H 2 O) 6 ](BF 4 ) 4 is observed in the same reaction as [Ni 2 (Cl2poap) 3 F](BF 4 ) 3 ·7.5H 2 O.…”
Section: Oligomers and Other Possible Alternative Products To The 'Exmentioning
confidence: 99%
“…Indeed, many polynuclear complexes of 2,6-pyridinediacylhydrazone have been reported [21][22][23][24][25][26][27][28][29]. It is interest to see that most of which are trinuclear complexes [2,30,31] and nonanuclear clusters with [3 9 3] grid-type architectures [23,[32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%